CARE OF TERMINALLY ILL CANCER PATIENTS: A TERTIARY CARE CENTRE SCENARIO IN BHOPAL - BHUPENDRA KUMAR RATRE; ROOPESH JAIN (International Journal of Pharma and Bio Sciences, 2013)
Admissions of terminally ill cancer patients are a great challenge whenever they get admitted in icu. There is always a delima in dealing such patients for a intensivist. To identify the benefits of critical care. To find out whether utilization of resources for intensive care has got any positive outcome in terminally ill cancer patients. A retrospective evaluation of 53 terminally ill cancer patients, who got admitted to ICU of our department, was carried out. Majority of these patients presented with terminal phase of illness involving multi-organ pathologies diverse range of symptoms.These patient provided cardiac-respiratory support and symptomatic and supportive care according to need and indication. All patients were monitored in ICU for hemodynamic and respiratory stability. The demographic profile of such patients was highly variable with regards to educational, social and financial status (P<0.05). The most common group of cancer was hematological malignancies (24.53%) followed by lung cancer (18.87%), uteri-ovarian (15.09), colorectal (13.2%) and others. Significant number (P<0.05) of patients (64.15%) required mechanical ventilation and ionotropic support (79.24%). Mortality increased with increasing number of organ system involvement and reaching up to 100% with involvement of 5 or more organ systems ICU care is the best form of treatment for terminally ill but resources should be used optimally so that a young deserving patient should not be sacrificed for the scarcity of resources.